Experiences of farmers-herders conflicts in Nigeria - Momale, Saleh; Flintan, Fiona E.; Nassef, Magda; Higazi, Adam (CGIAR System Organization, 2024)
A presentation made at a regional roundtable at the Colloquim on (Agro)Pastoralism, Senegal, 12-14th November, 2024.